Encapsulated Fe3O4 nanoparticles with silica thin layer as an anode material for lithium secondary batteries - Park, Sang-Eun; Lee, Sang-Wha; Yang, Daniel; Lee, Joong Kee (IOP PUBLISHING LTD, 2010)
Fe3O4 nanoparticles were coated with a SiO2 layer by using a modified sol-gel method. The synthetic procedures for Fe3O4 nanoparticles encapsulated with a SiO2 layer (SiO2@Fe3O4) consist of three consecutive steps: (i) fabrication of Fe3O4 by the co-precipitation method, (ii) stabilization of Fe3O4 with citrate as a capping agent, which is used to prevent particles from aggregating, and (iii) silica encapsulation by a modified sol-gel reaction. Based on the experimental range, SiO2@Fe3O4 exhibited higher cyclic performance than the intrinsic one. The reversible capacity of Fe3O4 with SiO2 at the first cycle was 363 mA h g(-1) and the remaining discharge capacity was 321 mA h g(-1) after the 30th cycle.
Keywords: ION BATTERIES; ELECTROCHEMICAL PROPERTIES; NANOCOMPOSITE; ELECTRODES; MATRIX